Visual evoked potentials and pulse wave velocity in inflammatory bowel disease - Aytaç, Erman; Büyüktaş, Deram; Baysal, Birol; Atar, Murat; Yıldız, Mustafa; Baca, Bilgi; Karahasanoğlu, Tayfun; Çelik, Aykut; Seymen, Hakki Oktay; Hamzaoğlu, İsmail (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Data about the effects of inflammatory bowel disease (IBD) on various functions of the nervous and cardiovascular systems are limited. In this study, the visual neuronal and cardiovascular functions of patients with IBD were evaluated by measuring visual evoked potentials (VEP) and pulse wave velocity (PWV), respectively. Materials and Methods: There were three study groups: the Crohn’s disease (CD) group (n=25), the ulcerative colitis (UC) group (n=30), and a healthy control (C) group (n=25). The exclusion criteria were as follows: patients with IBD were in remission, had no extra-intestinal manifestations of the disease, had no additional chronic disease(s), and had been receiving medical treatment for their IBD without any previous surgical intervention. VEP amplitudes (mV) and the N2 and P2 latencies (ms) were recorded for visual-neuronal analysis of all study groups. For cardiovascular assessment in all study groups, PWV was measured noninvasively as follows: the carotid-femoral PWV with the Complior Colson device (The authors have no conflict of interest.) and the PWV along the aorta with two ultrasound strain-gauge pressure-sensitive transducers (TY-306 Fukuda pressure-sensitive transducers - Fukuda Denshi Co, Tokyo, Japan) fixed transcutaneously over the course of a pair of arteries separated by a known distance. The right femoral and right common carotid arteries were the ones used. Results: The PWV levels of the CD and UC groups were significantly higher than those in the C group (p<0.001). In the bilateral recording of the VEP, the N2 latencies of the CD (p<0.05) and UC (p<0.01) groups were significantly longer than those in the C group. Conclusion: In this study, we showed vascular and visual neuronal impairments at a subclinical stage in patients with both types of IBD.